ITGA1 Promotes Glioma Cell Proliferation and Affects Immune Cell Infiltration in Low-Grade Glioma - Yanhong Ren; Jianchang Xu; Zhengkui Zhang; Rutong Yu (Mediators of Inflammation)
Conclusion: High ITGA1 expression is correlated with immune infiltration of the low-grade tumor, leading to poor prognoses in LGG patients.